PENINGKATAN KEMAMPUAN DAN PEMAHAMAN PELAKU UMKM DALAM MENGHADAPI PANDEMI DI DESA UJONG TANJONG, MEUREUBO, ACEH BARAT - Yenny Ertika; Nabila Hilmy Zhafira; Okta Rabiana Risma; Filia Hanum (Universitas Teuku Umar, 2021)
ABSTRACTCovid-19 has an impact on Micro, Small and Medium Enterprises (MSME), so efforts are needed to maintain MSME productivity during the pandemic for the stability of the income of the perpetrators. Through continuous programs to foster a business mentality and culture, product design creativity, absorption of technological advances, as well as managerial knowledge and skills that are in line with the demands of a constantly changing business environment. The purpose of this community service activity is to provide training on entrepreneurship to business actors and the community so that they can run their business and be able to compete in order to achieve prosperity. From the results of the implementation of Community Service, the training participants responded positively and looked satisfied. Some of the efforts that can be made by MSMEs for the Usaha Kerupuk Gurih Cahaya to increase their income are by learning more details about technology, providing good service to consumers and paying attention to the quality of the products to be sold to consumers. In addition, we also recommend survival strategies that MSMEs can do by trading through e-commerce, digital marketing, adding services to consumers, optimizing marketing relationships with consumers, and maintaining products and maintaining existing customers.Keyword : Covid-19, UMKM, Pendapatan dan Strategi